Pharmocological activity and phytochemical analysisofcoldenia procumbens linn - P.JAYARAMAN; V.RAJESH; R.LOGAMBAL (International Journal of Pharma and Bio Sciences, 2018)
Analysis of Phytochemical constituents and the ant diabetic & anti-oxidant activity of the medicinally important plant species Coldenia procumbens Linn. Collected from Thamanur village of Gingee Fort in Villupuram district of Tamil nadu, India was carried out in the present study. The fresh leaves of the above plant were used after they were dried and powdered for extraction with methanol solvent. The crude extracts were screened for the presence of phytochemical constituents and found with the presence of phenols, terpenoids and tannins in significant level and flavonoids and saponins at moderate level in the crude extracts from the leaves of Coldenia procumbens. The quantitative estimation of phenols and flavonoids were determined and found to be 315.63 GAE/g (Gallic acid equivalent) and 166.54 QE/g (Qurcetin equivalent) respectively. The anti-diabetic activity of methanolic crude extract of the above plant was assayed and observed as 53% (at 1000µl conc.) for Glucose uptake by Yeast cells assay, 21.96% (at conc. 125μg/ml) for inhibition of α-amylase activity test and 77.52% (at conc. 1250mg/ml) for Non-enzymatic glycosylation of Hemoglobin assay. For the antioxidant activity of the plant leaf extract, it showed a maximum of 78% by DPPH assay (at conc. 600 µg/mL), the scavenging activity reached 0.197 – 0.737% (conc. of 50 - 350µl) for Phosphomolybdenum assay and 17.08 to 65.57% (concentration from 50 - 350µl) for Nitric oxide scavenging assay. Thin Layer Chromatography (TLC) was performed on crude compound and observed the separation of 6 bioactive compounds at the RF value of 0.24, 0.38, 0.44, 0.57 and 0.64 as red color in UV light and brown color in iodine vapour with additional compound at the RF value of 0.90. From the present study, it was found that methanolic leaf extract of C. procumbens leaves possessed high anti-diabetic and antioxidant activity and found to have potential phytochemical compounds.